Свійські та дикі ссавці з Давньоруського Пастирського городища - Журавльов, О.П. (Археологія, 1998)
У статті наводиться характеристика свійських та диких ссавців, кістки яких знайдено під час розкопок Пастирського городища. Зроблено висновки про своєрідність тваринництва на ньому. В статье дана характеристика домашним и диким млекопитающим, кости которых были найдены при раскопках Пастырского городища, датируемого второй половиной VII — VIII в. н. э. Сделаны выводы о своеобразии животноводства на этом городище (преобладание домашних свиней и значительный процент мелкого рогатого скота), а также породного состава домашнего быка, которые не имели аналогов среди древнерусских памятников Среднего Поднепровья. The paper presents the characteristics of domestic and wild mammals, the osteological findings of which were investigated in Pastyr settlement attributed to the second half of 7th and 8th AD. The author draws inference about distinctive quality of the cattle-breeding in the settlement (predominance of domestic pigs and significant percentage of sheep and goats) and pedigreed structure of domestic bull herds; the latter is unrivalled among the Ancient Rus’ sites in the Middle Dnieper.